Pengaruh Temperatur Pemanasan dan Pendinginan Terhadap Sifat Mekanik Pada Proses Annealing Baja AISI410 Setelah Pengerasan - BAYU PRANOTO; Subagiyo Subagiyo; Samsul Hadi (Jurnal Energi dan Teknologi Manufaktur, 2022)
Stainless steel has good mechanical properties compared to other materials for strength and hardness, usually will experience an increase in hardness after hardening. The purpose of this study was to obtain information about: Value of hardness and strength Impact of martensitic stainless steel annealed with variations in temperature and cooling. The research method used is an experimental method, namely by annealing martensitic stainless steel with variations in temperature and cooling rate. The results were tested for Impact and hardness using the Rockwell C (HRC) method with the category of Research Infrastructure development and science and technology in the field of Mechanical Engineering. The research results are expected to be used as an alternative to improve the mechanical properties of materials, especially in the annealing process. The level of technological readiness to be achieved: 2, because in this study a model is made to test the truth of the basic principle that the hardness level of martensitic steel in annealing is influenced by varying temperatures and cooling.